Bulk magnetic domain stability controls paleointensity fidelity - Paterson,GA; Muxworthy,AR; Yamamoto,Y; Pan,Y (Proceedings of the National Academy of Sciences, 2017)
Nonideal, nonsingle-domain magnetic grains are ubiquitous in rocks; however, they can have a detrimental impact on the fidelity of paleomagnetic records—in particular the determination of ancient magnetic field strength (paleointensity), a key means of understanding the evolution of the earliest geodynamo and the formation of the solar system. As a consequence, great effort has been expended to link rock magnetic behavior to paleointensity results, but with little quantitative success. Using the most comprehensive rock magnetic and paleointensity data compilations, we quantify a stability trend in hysteresis data that characterizes the bulk domain stability (BDS) of the magnetic carriers in a paleomagnetic specimen. This trend is evident in both geological and archeological materials that are typically used to obtain paleointensity data and is therefore pervasive throughout most paleomagnetic studies. Comparing this trend to paleointensity data from both laboratory and historical experiments reveals a quantitative relationship between BDS and paleointensity behavior. Specimens that have lower BDS values display higher curvature on the paleointensity analysis plot, which leads to more inaccurate results. In-field quantification of BDS therefore reflects low-field bulk remanence stability. Rapid hysteresis measurements can be used to provide a powerful quantitative method for preselecting paleointensity specimens and postanalyzing previous studies, further improving our ability to select high-fidelity recordings of ancient magnetic fields. BDS analyses will enhance our ability to understand the evolution of the geodynamo and can help in understanding many fundamental Earth and planetary science questions that remain shrouded in controversy.